PENGARUH KECEMASAN MATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI SE-KECAMATAN BANYUASIN - Ika Septiarini; Nila Kesumawati; Jumroh Jumroh (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2020)
This study aims to find out the relationship, influence, and how much influence of mathematical anxiety on the mathematical problem solving ability of smp negeri students in Rambutan Banyuasin sub-district. This research is quantitative research using survey method. Data collection with tests and engket. The data collected were analyzed using correlation analysis techniques namely normality test, linearity test, and correlation test. From the results of the study, it was concluded that mathematical anxiety has a relationship and influence on the mathematical problem solving ability of junior high school students in Rambutan Banyuasin sub-district.